Disseminated Cryptococcosis with Marked Eosinophilia in a Postpartum Woman - Yokoyama, Tetsuya (Intern Med, 2017)
Disseminated cryptococcosis usually develops in immunosuppressed patients. A 33-year-old postpartum woman developed disseminated cryptococcosis with marked eosinophilia. She presented with a cough and a week-long fever. A computed tomography scan showed multiple pulmonary nodules randomly distributed. Eosinophils were observed to have increased in number in both her peripheral blood and bronchoalveolar lavage fluid. A transbronchial lung biopsy and cerebrospinal fluid specimens revealed findings consistent with cryptococcal infection. Disseminated cryptococcosis can present with marked eosinophilia of the peripheral blood and lung tissues. Additionally, the postpartum immune status may sometimes be involved in the development of opportunistic infections in previously healthy women.